2021
DOI: 10.3389/fnut.2021.733591
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Bacillus amyloliquefaciens 40 Against Clostridium perfringens Infection in Mice

Abstract: This study aimed to investigate the protective effects of Bacillus amyloliquefaciens (BA40) against Clostridium perfringens (C. perfringens) infection in mice. Bacillus subtilis PB6 was utilized as a positive control to compare the protective effects of BA40. In general, a total of 24 5-week-old male C57BL/6 mice were randomly divided into four groups, with six mice each. The BA40 and PB6 groups were orally dosed with resuspension bacteria (1 × 109 CFU/ml) once a day, from day 1 to 13, respectively. In the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…Using the broiler model which was infected by C. perfringens , the pro-apoptosis related genes also showed a significant increase ( P < 0.05) and a dramatic decrease ( P < 0.05) in anti-apoptosis related genes ( 56 ). Our previous study presented the same results, C57B/L mice infected with C. perfringens ATCC 13124 showed a significant decrease in jejunal Bcl-2 gene expression and a significant increase in Bax, p53, Caspase-3 and Caspase-9 gene expression ( 21 ). In the present study, we found that the High group can induce a stronger apoptosis signal compared with other groups.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Using the broiler model which was infected by C. perfringens , the pro-apoptosis related genes also showed a significant increase ( P < 0.05) and a dramatic decrease ( P < 0.05) in anti-apoptosis related genes ( 56 ). Our previous study presented the same results, C57B/L mice infected with C. perfringens ATCC 13124 showed a significant decrease in jejunal Bcl-2 gene expression and a significant increase in Bax, p53, Caspase-3 and Caspase-9 gene expression ( 21 ). In the present study, we found that the High group can induce a stronger apoptosis signal compared with other groups.…”
Section: Discussionsupporting
confidence: 65%
“…It is known that the physical barrier is the first line of defense against pathogens invading into the intestine, and gut health level is related to villus atrophy and crypt hyperplasia degree ( 33 ). Our previous study indicated that C. perfringens infection can trigger serious villous atrophy and intestinal morphology disruption ( 21 ). This study also demonstrated that High dose C. perfringens inoculation impaired the development of the small intestinal morphology, weakened the villus morphology, decreased the ratio of villus height/crypt depth, and triggered an irreparable effect on the crypt depth in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data regarding microbiota community were analyzed using the free online Majorbio Cloud Platform. Metagenomes were predicted from the copy number-normalized 16S rRNA data according to a previous report ( Jiang et al, 2021 ). Differences were considered statistically significant at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%